Seleksi Pemilihan Karyawan Terbaik Menggunakan Metode Profile Matching - Akbar, Muhammad Dean; Mufty, Mufty (LPPM UNIKA Santo Thomas Medan, 2020)
Appreciation of a performance for the best employees is something that must be done by a company to encourage employees to be more enthusiastic in working. Reward is given to employees who have performed the best in the last year, while the awarding of a letter of reprimand is given to employees who have very poor performance. the selection of the best employees so far is based only on attendance and observation from the assessment of performance in one year regardless of other criteria of assessment. so there are often mistakes in choosing the best employees. in this study using Profile Matching method in performing calculations and employee rank. The results showed that employees on behalf of Serly were selected as the best employees with a score of 4.96